LOW-COST TECHNOLOGY FOR RECOVERY ENVIRONMENT - , А. В. (Municipal economy of cities. Series: «Economy science», 2013)
Analyzes the international experience improvement of water resources by higher aquatic vegetation, described the relevant mechanisms. The classification of the main forms of phytoremediation, particularly for water purification. Definitely possibility of using methods in question, given the type of contamination and the natural vegetation.